Q 1: If a=2, b=3, and c=4, then check if the following statement is true or false. (ab)^{3} = (ab)(a^{2}2ab+b^{2}). False True

Q 2: If a=3, b= 5, and c=3, then check if the following statement is true or false.
(a+b)^{2} = a^{2}+2ab+b^{2}. True False

Q 3: If a=2, b=3, and c=3, then check if the following statement is true or false.
(a+b)^{2}+(ab)^{2} = 2a^{2}+2b^{2}. True False

Q 4: If a=0, b=2, and c=4, then check if the following statement is true or false. (a+b+c)^{2} = a^{2}+b^{2}+c^{2}+2ab+2bc+2ca. True False

Q 5: If a=0, b=1, and c=2, then check if the following statement is true or false. (ab+c)^{2} = a^{2}+b^{2}+c^{2}2ab2bc+2ca. False True

Q 6: If a=4, b=3, and c=2, then check if the following statement is true or false. (a+b)^{3} = (a+b)(a^{2}+2ab+b^{2}). True False

Q 7: If a=3, b=5, and c=3, then check if the following statement is true or false.
b^{2}c^{2} = (b+c)(bc). False True

Q 8: If a=3, b=0, and c=3, then check if the following statement is true or false. (a+bc)^{2} = a^{2}+b^{2}+c^{2}+2ab2bc2ca. True False

Question 9: This question is available to subscribers only!

Question 10: This question is available to subscribers only!

